THE INFLUENCE OF RETURN ON ASSETS AND EARNINGS PER SHARE ON SHARE PRICE AT. BANK RAKYAT INDONESIA, TBK - Karolina, Karolina (International Journal of Social and Management Studies, 2023)
The purpose of this study was to determine the effect of Return on Assets and Earning per Share on stock prices at PT. Bank Rakyat Indonesia, Tbk for the period 2012 to 2021. This research uses quantitative research methods and the data used is secondary data. The sample in this study is financial report data, namely the income statement at PT. Bank Rakyat Indonesia, Tbk for the period 2012 to 2021. The data analysis method used is descriptive test, classic assumption test (Normality, Multicollinearity, Heteroscedasticity, and Autocorrelation), simple linear regression test, multiple linear regression test, hypothesis testing and coefficient of determination. The analytical tool used is SPSS version 25. The results of this study indicate that Return on Assets partially has a negative and significant effect on stock prices with a significance of 0.035 <0.05 and –t count < -t table (-2.609 < -2.364), so also Earning per Share which partially has a negative and significant effect on Stock Price with a significance value of 0.046 <0.05 and t count < -t table (-2.421 < -2.364). Then the results of this study indicate that simultaneously Return on Assets and Earning per Share have a positive and significant effect on stock prices with a significance value of 0.001 <0.05 and F count > F table (22.306 > 4.74) and a contribution of 86.4% to changes in stock prices while the remaining 13.6% is explained by other variables not included in the regression model